State-of-the-art cytometry in the search of novel biomarkers in digestive cancers - G. de Castro, Carolina; G. del Hierro, Alejandro; H-Vázquez, Juan; Cuesta-Sancho, Sara; Bernardo, David (Frontiers in Oncology, 2024)
Despite colorectal and liver cancer are among the most prevalent tumours in the world, the identification of non-invasive biomarkers to aid on their diagnose and subsequent prognosis is a current unmet need that would diminish both their incidence and mortality rates. In this context, conventional flow cytometry has been widely used on the screening of biomarkers with clinical utility in other malignant processes like leukaemia or lymphoma. Therefore, in this review we will focus on how advanced cytometry panels covering over 40 parameters can be applied on the study of the immune system from patients with colorectal and hepatocellular carcinoma, and how that can be used on the search of novel biomarkers to aid or diagnose, prognosis and even predict clinical response to different treatments. Besides, these multiparametric and unbiased approaches can also provide novel insights into the specific immunopathogenic mechanisms governing these malignant diseases, hence potentially unravelling novel targets to perform immunotherapy or identify novel mechanisms hence rendering to the development of novel treatments. As a consequence, computational cytometry approaches are an emerging methodology for the early detection and predicting therapies for gastrointestinal cancers.